Klippel-Trenaunay-Weber Syndrome – A Rare Case with Visceral Manifestation and Thrombosed Marginal Vein of Servelle - Ibrahim, Muhammad Imran; Hussain Awan, Leena; Khan, Babar; Javed, Koukab; Mariam Zehra, Syeda; Hussain, Mariam (Pakistan Armed Forces Medical Journal, 2022)
Klippel-Trenaunay-Weber syndrome is a rare congenital syndrome characterized by capillary, venous or lymphaticmalformation and hemihypertrophy. Only 1000 cases of this syndrome have been reported in the literature. A rare case of this syndrome is presented here, who presented with its visceral and vascular complications and was diagnosed for the first time.